Evaluation and comparison of biomarkers in heart failure - Sudharshana Murthy, K.A. (Indian Heart J, 2016)
OBJECTIVES: To establish biomarkers available as predictors of prognosis and mortality in heart failure (HF) patients and to correlate the biomarkers with the severity and outcome of HF. METHODS: This was a prospective study. 60 patients of HF were taken into the study based on the inclusion and exclusion criteria and were studied for the markers – BNP, TNF-α, troponin-I, CK-MB, CRP, uric acid, GGT and were compared with the severity and outcome in these patients. RESULTS: Of 27 patients with BNP value less than 100 pg/ml, only 1 death occurred (3.7%) and out of 33 patients with BNP value of more than 100 pg/ml, 8 deaths occurred (24.2%). Out of the 9 deaths that had occurred, 7 deaths were in the troponin range of >0.5 ng/ml, 2 deaths in the troponin range of 0.04–0.49 ng/ml, and no deaths in the range of 0–0.03 ng/ml. 8 deaths had an elevated titer of TNF (40%) and 39 patients out of 40 were survivors who had TNF titers in the normal range (97.5%). CONCLUSION: BNP and TNF-α are excellent predictors of mortality and morbidity in HF. Troponin-I and CRP have shown significance in predicting the outcome in HF. GGT, uric acid, and CK-MB play no role in predicting the severity and outcome in HF.